Gambaran tentang Tingkat Kepuasan Pasien di Puskesmas Rawalo Kecamatan Rawalo Kabupaten Banyumas Tahun 2021 - Puska Andri Ana; Indri Heri Susanti; Danang Tri Yudono (Universitas Harapan Bangsa, 2021)
Patient satisfaction is one of the important indicators that must be considered in health services. Patient satisfaction is the result of the patient's assessment of health services by comparing what is expected in accordance with the reality of health services received. Patient satisfaction is the result of the patient's assessment of health services by comparing what is expected in accordance with the reality of the health services received. The purpose of this study was to describe the level of patient satisfaction at the Rawalo Health Center, Rawalo District, Banyumas Regency in 2021.). The variables involved in this study are single variables, namely the level of patient satisfaction. The sample in this study was calculated using the Slovin formula with the results of 93 samples.The results showed that the majority of respondents (32%) were in the age category 25-34 years, the average gender was female (77%), and most of them worked as laborers (57%). Of all respondents stated satisfied 93 (100%) with a range of values ​​(47-115